POLITIK KEKERABATAN - Anggariani, Dewi (JPP (Jurnal Politik Profetik), 2013)
Human being is ‘zoon politicon’ and human being lives to get involved in politics. This classic statement by Aristotles is still relevant to relate to the political system within the community today. Political structure was established to enhance and to fulfill all needs of human life. Due to this, political system may be applied to all walks of life. For common people, political structure is mainly based on family tree and bloodlines.